Language learning strategies: A study among Spanish students in the University of Malaya - Neo, Swee Leng Pauline (Journal of Modern Languages, 2017)
This study investigates the types of strategies generally used by students in one of the institutions of higher learning in Malaysia in the course of learning Spanish and the relationship between the use of these strategies and other factors such as ethnicity, motivation and language proficiency level. The subjects of this study consist of first, second and third year Spanish students from the Faculty of Languages and Linguistics, University of Malaya and the research data was collected using the background questionnaire, Strategy Inventory for Language learning (SILL) adapted from Oxford (1990b) and interviews. The findings indicate that generally, the use of language learning strategy is not very common among the students in this faculty. For those who apply the strategies, metacognitive types were used more often while affective strategies were shunned. Among the ethnic groups involved in this research, the Malay students top the list of those who use learning strategies. Students with high motivation use language learning strategies more often than those with lower motivation. Likewise, excellent students use language learning strategies more than average and weak students.